Illusions of Emancipation : The Pursuit of Freedom and Equality in the Twilight of Slavery - Reidy, Joseph P. (Joseph Patrick), 1948- (Book collections on Project MUSE., 2019)
"There are many controversies and chronic misconceptions surrounding the idea of emancipation in the nineteenth-century United States. Much recent scholarship has sought to address these misconceptions ... Reidy further enriches and complicates our understanding of emancipation in the context of the Civil War. Drawing us back to testimonies of participants and contemporary witnesses of the era and synthesizing the perspectives of subsequent observers, Reidy reveals emancipation as a long, messy process, with contingencies that clustered around the categories of time, place, and person ... Reidy's thematic approach allows him to shed new light on the wide-ranging and diverse expressions and experiences of freedom as it came suddenly, slowly, or not at all"--